Preparation method and application of CaCoO3-based nano composite material
CaCoO3-based nanocomposites were prepared by sol-gel method and microwave treatment, which solved the problems under complex processes and high temperature conditions in the prior art, and achieved efficient and low-cost nanocomposite preparation, significantly improving catalytic performance.
Patent Information
- Application Number
- CN202510022152.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-11
AI Technical Summary
The existing CaCoO3 powder surface modification method has complex processes and needs to be carried out under a high-temperature reduction atmosphere. The dissolution reaction time of nanoparticles is long, which limits the preparation efficiency of CaCoO3-based nanocomposites.
The CaxCoO3 perovskite powder with absent position A was prepared by sol-gel method, and ultrasonic dispersed in weak oxidation or acidic solution. Then, topological chemical reaction and microwave heating treatment were carried out under microwave to prepare CaCoO3-based (Co3O4/CaCoO3) nanocomposite.
In situ desolution reconstruction on the surface of perovskite particles is achieved, and uniformly dispersed Co3O4 nanoparticles are formed, which improves the exposure of catalytic active sites and enhances catalytic performance. It has a simple process and low cost, which is suitable for industrial production.
Smart Images

Figure CN119800428A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of functional composite materials, and in particular relates to a preparation method and application of a CaCoO3-based nanocomposite material. Background Art
[0002] Perovskite oxide (ABO3) is considered to be the most promising material to replace precious metals as a catalyst for environmental protection and energy storage and conversion devices such as air purification, water electrolysis, fuel cells and metal-air batteries due to its good intrinsic electrocatalytic activity, flexible and controllable structure, low price and easy synthesis. In particular, perovskite cobalt oxide has high catalytic efficiency and good thermal stability, and has attracted much attention from scholars in the field of energy and environment. In 2019, Goodenough's research group prepared the CaCoO3 perovskite catalyst by high-pressure solid-phase reaction synthesis. CaCoO3 has a cubic crystal structure with long-range magnetic order, Co 4+ With electrons in the t4σ* intermediate spin state, the Co-O bond length is Therefore, it has a high electrical conductivity close to that of metal, and CoO 6 / 2 The octahedral sites have no synergistic John-Teller distortion and are the most catalytically active materials among the known oxygen evolution reaction (OER) catalysts [Li X, Wang H, Goodenough JB, et al, Science Advances, 2019, 5(9): 1-7.]. However, the CaCoO3 powder prepared by high-pressure solid-phase reaction synthesis has large particle size and low specific surface area, and the particle surface is occupied by catalytically inactive A-site cations. These characteristics severely limit its catalytic activity. Therefore, increasing the specific surface area of CaCoO3 perovskite powder and exposing more surface active sites are the key to realizing the practical application of perovskite catalysts.
[0003] At present, most methods of improving powder preparation process and modifying powder surface are used to reduce the particle size of perovskite powder and increase the active reaction area. For example, hydrothermal synthesis method [Liao Jinsheng, Kong Liyun, Wang Minghua, Peng Guanghuai, Journal of Luminescence, 2019, 40(12): 1486-1493] and template method [Ji K, Dai H, Deng J, et al, Applied Catalysis A: General, 2012, 425-426: 153-160] are used to control the particle size and morphology of perovskite powder. However, due to the limitation of reaction conditions, these methods can only be used for the synthesis of some perovskite materials, and these preparation methods still need to be calcined at high temperature later, and the actual performance improvement is limited. The surface modification of perovskite powder generally adopts mechanical mixing, physical deposition and in-situ growth methods [Zhang M, Jeerh G, Zou P, et al, Materials Today, 2021, 49(10): 351-377]. The mechanical mixing method is difficult to form a stable two-phase interface, and the interface bonding force is weak; the physical deposition method has expensive equipment, and the surface modification phase is uneven, and it is easy to show the self-agglomeration phenomenon of the modified phase; the in-situ precipitation method can realize the in-situ precipitation of nano-metal or alloy particles on the surface of perovskite. The precipitated nanoparticles are evenly distributed on the surface of the perovskite matrix and firmly bonded to the matrix. It is a hot method for perovskite surface modification research in recent years. However, due to the slow solid-phase diffusion rate of cations in the perovskite lattice, the precipitation process of active atoms usually needs to be carried out under a high-temperature reducing atmosphere (H2 / 3% H2O), and the dissolution of nanoparticles requires a long reaction time. The whole process is not only very time-consuming, but also leads to uncontrollable agglomeration problems, resulting in a decrease in the specific surface area of the perovskite matrix and no obvious improvement in catalytic performance; in addition, extreme reducing conditions lead to the destruction of the main crystal phase of the perovskite [Li Y, Zhang W, Zheng Y, Chem. Soc. Rev., 2017, 46: 6345-6378]. Therefore, finding new desolvation methods is also an issue that should be considered while paying attention to the advantages of surface desolvation nanoparticles.
[0004] Since the existing technology does not have a green, low-cost and efficient preparation process for CaCoO3-based nanocomposites, the development of this high-performance material is limited. Summary of the invention
[0005] The purpose of the present invention is to solve the problems that the existing CaCoO3 powder surface modification methods are complicated, the existing desolvation and in-situ precipitation method needs to be carried out in a high-temperature reducing atmosphere, and the dissolution reaction time of nanoparticles is long, and to provide a method for preparing CaCoO3-based nanocomposites by in-situ desolvation and reconstruction on the surface of perovskite particles in a gentle manner.
[0006] The preparation method of the CaCoO3-based nanocomposite material of the present invention is achieved by the following steps:
[0007] 1. Preparation of Ca2+ with A-site vacancy by sol-gel method x CoO3 perovskite powder;
[0008] 2. diluting the weakly oxidizing or acidic material with deionized water to obtain a solution a with a concentration of 0.1 to 2 mol / L;
[0009] 3. Replace the missing Ca x CoO3 perovskite powder is ultrasonically dispersed in solution a, and then heated in a water bath at 30-90°C, and the topological chemical reaction time is adjusted to 0.2-8h to obtain a dispersion;
[0010] 4. Centrifugally separating the dispersion obtained in step 3, washing the solid phase with deionized water and anhydrous ethanol, respectively, and drying to obtain a composite material precipitate;
[0011] 5. subjecting the composite material precipitate obtained in step 4 to microwave heating to obtain a CaCoO3-based (Co3O4 / CaCoO3) nanocomposite material;
[0012] The weakly oxidizing or acidic material in step 2 is sulfonic acid amine, boric acid (H3BO3), sodium borohydride, ethylene glycol or hydrogen peroxide.
[0013] The application of the CaCoO3-based nanocomposite material of the present invention is to use the CaCoO3-based nanocomposite material as an oxygen evolution reaction (OER) catalyst.
[0014] The present invention uses a weakly oxidizing or acidic substance as a control agent for the dissolution of CaO at the A position of the perovskite and the surface desolvation and reconstruction of Co3O4 at the activation position B, and enhances the Co3O4 / CaCoO3 heterogeneous interface structure through microwave excitation to prepare a CaCoO3-based nanocomposite material. The advantages are that the raw materials are generally available, the cost is low, the preparation process is safe, and it is simple and easy; in the obtained product, the Co3O4 nanoparticles are uniformly dispersed on the surface of the CaCoO3 matrix, fully exposing the catalytic active sites, and there are no metal oxide particles that are separated from the external nucleation growth of the CaCoO3 surface, and the problem of the catalyst specific surface area being reduced due to the agglomeration of the externally loaded metal oxide particles is effectively avoided. The optimization of the microstructure of the composite material makes it have good comprehensive performance and potential application value in more fields.
[0015] The invention provides a method for preparing a high-performance CaCoO3-based nanocomposite material which is simple to operate and suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1is the XRD spectrum of the CaCoO3-based nanocomposite material prepared in Example 1;
[0017] Figure 2 is a SEM electron microscope photograph of the CaCoO3-based nanocomposite material prepared in Example 1;
[0018] Figure 3 is a linear polarization curve (IR compensation) diagram of the CaCoO3-based nanocomposite material used as an oxygen evolution reaction (OER) catalyst in Example 1;
[0019] Figure 4 This is an overpotential (IR compensation) test diagram of the CaCoO3-based nanocomposite material used as an oxygen evolution reaction (OER) catalyst in Example 1;
[0020] Figure 5 is a Tafel slope diagram of the CaCoO3-based nanocomposite material used as an oxygen evolution reaction (OER) catalyst in Example 1;
[0021] Figure 6 The CaCoO3-based nanocomposite material in Example 1 is used as an oxygen evolution reaction (OER) catalyst at 10 mA·cm -2 Chronopotentiometry curve (IR compensation) when . DETAILED DESCRIPTION
[0022] Specific implementation method 1: The preparation method of the CaCoO3-based nanocomposite material in this implementation method is implemented according to the following steps:
[0023] 1. Preparation of Ca2+ with A-site vacancy by sol-gel method x CoO3 perovskite powder;
[0024] 2. diluting the weakly oxidizing or acidic material with deionized water to obtain a solution a with a concentration of 0.1 to 2 mol / L;
[0025] 3. Replace the missing Ca x CoO3 perovskite powder is ultrasonically dispersed in solution a, and then heated in a water bath at 30-90°C, and the topological chemical reaction time is adjusted to 0.2-8h to obtain a dispersion;
[0026] 4. Centrifugally separating the dispersion obtained in step 3, washing the solid phase with deionized water and anhydrous ethanol, respectively, and drying to obtain a composite material precipitate;
[0027] 5. subjecting the composite material precipitate obtained in step 4 to microwave heating to obtain a CaCoO3-based (Co3O4 / CaCoO3) nanocomposite material;
[0028] The weakly oxidizing or acidic material in step 2 is sulfonic acid amine, boric acid (H3BO3), sodium borohydride, ethylene glycol or hydrogen peroxide.
[0029] The invention provides a method for preparing a CaCoO3-based nanocomposite material, which can in-situ dissolve and grow Co3O4 nanoparticles on the surface of a CaCoO3 matrix, wherein the Co3O4 nanoparticles have uniform particle size, and the particle size and loading amount are controllable, and the binding force with CaCoO3 is strong. First, a CaCoO3 perovskite powder is prepared by a sol-gel method, and then the prepared CaCoO3 is dispersed in a weakly oxidizing or acidic solution to obtain a uniform dispersion of CaCoO3; the concentration of the dispersion, the water bath temperature and the immersion time are adjusted, and microwave excitation is assisted to cause a topological chemical reaction on the surface of CaCoO3 to generate Co3O4; finally, the product is washed and vacuum dried to obtain a Co3O4 / CaCoO3 composite material with a heterogeneous structure. The invention has the advantages that the preparation process is simple and easy to control, the raw material cost is low, it is easy to obtain, and it is environmentally friendly; the prepared CaCoO3-based nanocomposite material has good composition and structural stability, and is used as an electrode material for water electrolysis, metal-air batteries, fuel cells, etc., with high catalytic activity, fast reaction speed, and good stability.
[0030] Specific embodiment 2: This embodiment is different from the specific embodiment 1 in that the Ca in the A position is absent in step 1. x Ca in CoO3 perovskite powder 2+ The stoichiometric ratio x is 0.82 to 0.98.
[0031] Specific embodiment 3: This embodiment is different from specific embodiment 1 or 2 in that the sol-gel method is used in step 1 to prepare the Ca2+ vacancy at the A site. x The process of CoO3 perovskite powder is as follows:
[0032] a. Dissolve calcium nitrate (Ca(NO3)2·4H2O) and cobalt nitrate (Co(NO3)2·6H2O) in deionized water at a molar ratio of x:1, add citric acid and ethylenediaminetetraacetic acid, and then adjust the pH of the system to 6-9 with ammonia water to obtain a mixed reaction solution;
[0033] b. heating the mixed reaction solution in a water bath at 80° C. until a gel is formed, and then drying and grinding to obtain a powder product;
[0034] c. Calcine the powder product at 800-1200°C to obtain Ca x CoO3 perovskite powder.
[0035] In this embodiment, the molar ratio of citric acid to the sum of metal ions in calcium nitrate and cobalt nitrate is controlled to be 0.9-2.0:1, and the molar ratio of ethylenediaminetetraacetic acid to the sum of metal ions in calcium nitrate and cobalt nitrate is controlled to be 1:1.
[0036] Specific embodiment 4: This embodiment is different from specific embodiment 3 in that the drying temperature in step b is 150-220°C.
[0037] Specific implementation mode 5: This implementation mode is different from specific implementation modes 1 to 4 in that step 2 is to prepare a solution a with a concentration of 0.2 to 0.9 mol / L.
[0038] This embodiment controls the concentration of solution a. When the concentration of solution a is too low, the size of the Co3O4 dissolved particles is too small and the dissolution rate is slow. When the concentration of solution a is too high, it is easy to cause Ca x Collapse of the CoO3 perovskite mother crystal structure.
[0039] Specific implementation method 6: This implementation method is different from the specific implementation methods 1 to 5 in that in step 3, the Ca 2+ vacant at the A position is replaced by the Ca 2+ vacant at the A position. x The CoO3 perovskite powder is ultrasonically dispersed in solution a for 20 to 40 minutes.
[0040] Specific embodiment 7: This embodiment is different from any one of specific embodiments 1 to 6 in that the topological chemical reaction temperature in step 3 is adjusted to 40-80° C. and the reaction time is 1-2.5 h.
[0041] Specific embodiment eight: This embodiment is different from any one of specific embodiments one to seven in that the drying temperature in step four is 80°C.
[0042] Specific embodiment 9: The difference between this embodiment and any one of specific embodiments 1 to 8 is that in step 5, the power of microwave heating is controlled to be 0.5 to 1.2 kW, and the microwave heating treatment time is 1 to 10 minutes.
[0043] Embodiment 1: The preparation method of the CaCoO3-based nanocomposite material of this embodiment is implemented according to the following steps:
[0044] 1. Preparation of Ca2+ with A-site vacancy by sol-gel method x The process of CoO3 (x = 0.9) perovskite powder is as follows:
[0045] a. Dissolve calcium nitrate (Ca(NO3)2·4H2O) and cobalt nitrate (Co(NO3)2·6H2O) in a molar ratio of 0.9:1 in deionized water, add citric acid and ethylenediaminetetraacetic acid, and then adjust the pH of the system to 6 with ammonia water to obtain a mixed reaction solution; control the molar ratio of citric acid to the sum of metal ions in calcium nitrate and cobalt nitrate to be 1.5:1, and the molar ratio of ethylenediaminetetraacetic acid to the sum of metal ions in calcium nitrate and cobalt nitrate to be 1:1;
[0046] b. Heating the mixed reaction solution in a water bath at 80° C. until a gel is formed, drying the mixture (drying at 180° C. for 10 hours) until the water and organic matter in the gel are completely volatilized to form a powder, and grinding the mixture to obtain a powder product;
[0047] c. The powder product was calcined at 1000°C for 12 hours to obtain Ca x CoO3 (x = 0.9) perovskite powder;
[0048] 2. Dissolve 1.9614 g of sulfonic acid amine (purity 99%) in 100 mL of deionized water to prepare a solution a with a concentration of 0.2 mol / L;
[0049] 3. Add 2g of Ca2+ to the A-site vacancy x CoO3 perovskite powder was ultrasonically dispersed in solution a for 30 min, and then subjected to a topological chemical reaction in a 60°C water bath under magnetic stirring for 1 h to obtain a dispersion;
[0050] 4. The dispersion in step 3 was centrifuged, and after removing the supernatant, the solid phase was repeatedly washed with deionized water and anhydrous ethanol, and vacuum dried at 80° C. for 12 h to obtain a composite material precipitate;
[0051] 5. The composite material precipitate obtained in step 4 was subjected to microwave heating at a power of 0.9 kW for 3 min to obtain a CaCoO3-based (Co3O4 / Ca 0.9 CoO3) nanocomposite materials.
[0052] Figure 1 Co3O4 / Ca 0.9 XRD test results of CoO3 composite materials, a in the figure is Ca 0.9 The peak of CoO3 is shown in Figure 1; b is the standard peak of Co3O4, thus confirming that Co3O4 / Ca 0.9 CoO3 composite materials. Figure 2 Co3O4 / Ca 0.9 SEM photo of CoO3 composite material. It can be seen from the figure that the ellipsoidal Ca 0.9CoO3 particles, with a particle size of 200-250nm, and the dissolved Co3O4 particles are discretely embedded in the Ca 0.9 There is no obvious agglomeration of Co3O4 particles on the surface of CoO3 matrix particles. Figure 3 For the use of Ca 0.9 CoO3 and Co3O4 / Ca 0.9 Polarization curve of OER catalyst prepared by CoO3 nanocomposite. -2 When the voltage is 1.48V and 1.42V, the OER reaction overpotential is 250mV and 190mV respectively. Figure 4 ), which is better than the precious metals IrO2 (400mV) and RuO2 (290mV) [Wang X, Dou Y, Xie Y, ACS Omega, 2020, 5: 12501~12515]; Figure 5 Ca 0.9 CoO3 and Co3O4 / Ca 0.9 Tafel slope diagram of CoO3 nanocomposite materials for OER catalysts, Co3O4 / Ca 0.9 CoO3(76.8mV·dec -1 ) The Tafel slope of the nanocomposite is higher than that of Ca 0.9 CoO3(94.2mV·dec -1 ) increased by 22.6%, and Co3O4 / Ca 0.9 The OER reaction kinetics of CoO3 nanocomposites is slightly higher than that of the noble metal catalyst RuO2 (80.4 mV·dec -1 ) and IrO2(86.3mV·dec -1 )[Wang X, DouY, XieY, et al., ACS Omega, 2020, 5: 12501-12515]; Figure 6 For the use of Ca 0.9 CoO3 and Co3O4 / Ca 0.9 CoO3 nanocomposite materials for OER catalyst preparation at a polarization current density of 10 mA cm -2 At 10 mA·cm -2 At the polarization current density of , during the test time of 300 min, Ca 0.9 CoO3 and Co3O4 / Ca 0.9 The OER voltage of CoO3 catalyst remains basically stable.
[0053] Embodiment 2: The preparation method of the CaCoO3-based nanocomposite material of this embodiment is implemented according to the following steps:
[0054] 1. Preparation of Ca2+ with A-site vacancy by sol-gel method x The process of CoO3 (x = 0.95) perovskite powder is as follows:
[0055] a. Dissolve calcium nitrate (Ca(NO3)2·4H2O) and cobalt nitrate (Co(NO3)2·6H2O) in a molar ratio of 0.95:1 in deionized water, add citric acid and ethylenediaminetetraacetic acid, and then adjust the pH of the system to 9 with ammonia water to obtain a mixed reaction solution; control the molar ratio of citric acid to the sum of metal ions in calcium nitrate and cobalt nitrate to be 1:1, and the molar ratio of ethylenediaminetetraacetic acid to the sum of metal ions in calcium nitrate and cobalt nitrate to be 1:1;
[0056] b. Heating the mixed reaction solution in a water bath at 80° C. until a gel is formed, drying the mixture (drying at 220° C. for 6 hours) until the water and organic matter in the gel are completely volatilized to form a powder, and grinding the mixture to obtain a powder product;
[0057] c. The powder product was calcined at 800°C for 20 hours to obtain Ca x CoO3 (x = 0.95) perovskite powder;
[0058] 2. Dissolve 3.1229 g of H3BO3 (purity 99%) in 100 mL of deionized water to prepare solution a with a concentration of 0.5 mol / L;
[0059] 3. Add 2g of Ca2+ to the A-site vacancy x CoO3 perovskite powder was ultrasonically dispersed in solution a for 30 min, and then heated in a 40°C water bath with magnetic stirring for 1.5 h to perform a topological chemical reaction to obtain a dispersion;
[0060] 4. The dispersion in step 3 was centrifuged, and after removing the supernatant, the solid phase was repeatedly washed with deionized water and anhydrous ethanol, and vacuum dried at 60° C. for 12 h to obtain a composite material precipitate;
[0061] 5. The composite material precipitate obtained in step 4 was subjected to microwave heating at a power of 0.6 kW for 5 min to obtain a CaCoO3-based (Co3O4 / Ca 0.95 CoO3) nanocomposite materials.
[0062] This embodiment uses Ca 0.95 CoO3 and Co3O4 / Ca 0.95 CoO3 nanocomposites were prepared as OER catalysts at current densities up to 10 mA cm -2 When the voltage is 1.47V and 1.41V, the OER reaction overpotential is 240mV and 180mV respectively; Co3O4 / Ca0.9 The Tafel slope of CoO3 nanocomposites is higher than that of Ca 0.9 CoO3 decreased by 24.8% and the polarization voltage remained stable during the 600-min test time.
[0063] Embodiment 3: The preparation method of the CaCoO3-based nanocomposite material of this embodiment is implemented according to the following steps:
[0064] 1. Preparation of Ca2+ with A-site vacancy by sol-gel method x The process of CoO3 (x = 0.85) perovskite powder is as follows:
[0065] a. Dissolve calcium nitrate (Ca(NO3)2·4H2O) and cobalt nitrate (Co(NO3)2·6H2O) in a molar ratio of 0.85:1 in deionized water, add citric acid and ethylenediaminetetraacetic acid, and then adjust the pH of the system to 8 with ammonia water to obtain a mixed reaction solution; control the molar ratio of citric acid to the sum of metal ions in calcium nitrate and cobalt nitrate to be 2:1, and the molar ratio of ethylenediaminetetraacetic acid to the sum of metal ions in calcium nitrate and cobalt nitrate to be 1:1;
[0066] b. Heating the mixed reaction solution in a water bath at 80° C. until a gel is formed, drying the mixture (drying at 160° C. for 12 hours) until the water and organic matter in the gel are completely volatilized to form a powder, and grinding the mixture to obtain a powder product;
[0067] c. The powder product was calcined at 1100°C for 9 hours to obtain Ca x CoO3 (x = 0.85) perovskite powder;
[0068] 2. Dissolve 8.826 g of sulfonic acid amine (purity 99%) in 100 mL of deionized water to prepare a solution a with a concentration of 0.9 mol / L;
[0069] 3. Add 2g of Ca2+ to the A-site vacancy x CoO3 perovskite powder was ultrasonically dispersed in solution a, and then subjected to a topological chemical reaction in a 60°C water bath under magnetic stirring for 2.5 hours after ultrasonic dispersion for 30 minutes to obtain a dispersion;
[0070] 4. The dispersion in step 3 was centrifuged, and after removing the supernatant, the solid phase was repeatedly washed with deionized water and anhydrous ethanol, and vacuum dried at 100° C. for 12 h to obtain a composite material precipitate;
[0071] 5. The composite material precipitate obtained in step 4 was subjected to microwave heating at a power of 1.0 kW for 7 min to obtain a CaCoO3-based (Co3O4 / Ca 0.95 CoO3) nanocomposite materials.
[0072] This embodiment uses Ca 0.85 CoO3 and Co3O4 / Ca 0.85 CoO3 nanocomposites were prepared as OER catalysts at current densities up to 10 mA cm -2 When the voltage is 1.45V and 1.40V, the OER reaction overpotential is 220mV and 170mV, respectively. 0.9 The Tafel slope of CoO3 nanocomposites is higher than that of Ca 0.9 CoO3 decreased by 29.6%; and the polarization voltage remained stable during the 900min test time.
Claims
1. A method for preparing a CaCoO3-based nanocomposite material, characterized in that The preparation method of the CaCoO3-based nanocomposite material is achieved by the following steps:
1. Preparation of Ca2+ with A-site vacancy by sol-gel method x CoO3 perovskite powder; 2. diluting the weakly oxidizing or acidic material with deionized water to obtain a solution a with a concentration of 0.1 to 2 mol / L; 3. Replace the missing Ca x CoO3 perovskite powder is ultrasonically dispersed in solution a, and then heated in a water bath at 30-90°C, and the topological chemical reaction time is adjusted to 0.2-8h to obtain a dispersion; 4. Centrifugally separating the dispersion obtained in step 3, washing the solid phase with deionized water and anhydrous ethanol, respectively, and drying to obtain a composite material precipitate; 5. subjecting the composite material precipitate obtained in step 4 to microwave heating to obtain a CaCoO3-based nanocomposite material; The weakly oxidizing or acidic material in step 2 is sulfonic acid amine, boric acid, sodium borohydride, ethylene glycol or hydrogen peroxide.
2. The method for preparing the CaCoO3-based nanocomposite material according to claim 1, characterized in that The Ca vacancy at position A in step 1 x Ca in CoO3 perovskite powder 2+ The stoichiometric ratio x is 0.82 to 0.
98.
3. The method for preparing the CaCoO3-based nanocomposite material according to claim 1, characterized in that In step 1, the sol-gel method is used to prepare the Ca2+ vacancy at the A site. x The process of CoO3 perovskite powder is as follows: a. Dissolve calcium nitrate and cobalt nitrate in a molar ratio of x:1 in deionized water, add citric acid and ethylenediaminetetraacetic acid, and then adjust the pH of the system to 6-9 with ammonia water to obtain a mixed reaction solution; b. heating the mixed reaction solution in a water bath at 80° C. until a gel is formed, and then drying and grinding to obtain a powder product; c. Calcine the powder product at 800-1200°C to obtain Ca x CoO3 perovskite powder.
4. The method for preparing the CaCoO3-based nanocomposite material according to claim 3, characterized in that The drying temperature in step b is 150-220°C.
5. The method for preparing the CaCoO3-based nanocomposite material according to claim 1, characterized in that Step 2: Prepare solution a with a concentration of 0.2 to 0.9 mol / L.
6. The method for preparing the CaCoO3-based nanocomposite material according to claim 1, characterized in that In step 3, the Ca2+ vacancy at position A is x The CoO3 perovskite powder is ultrasonically dispersed in solution a for 20 to 40 minutes.
7. The method for preparing the CaCoO3-based nanocomposite material according to claim 1, characterized in that In step 3, the topological chemical reaction temperature is adjusted to 40-80° C., and the reaction time is 1-2.5 h.
8. The method for preparing the CaCoO3-based nanocomposite material according to claim 1, characterized in that The drying temperature in step 4 is 80°C.
9. The method for preparing the CaCoO3-based nanocomposite material according to claim 1, characterized in that In step 5, the power of microwave heating is controlled to be 0.5-1.2 kW, and the microwave heating treatment time is 1-10 min.
10. The use of the CaCoO3-based nanocomposite material prepared as claimed in claim 1, characterized in that The CaCoO3-based nanocomposite material is used as an oxygen evolution reaction catalyst.